EXERGOECONOMIC MODEL ON POWER AND CHILLED WATER COST RATES FOR GAS-FUELED DISTRICT COOLING SYSTEM - NORDIN, ADZUIEEN (2017)
The aim of this study is to propose an exergoeconomic model for the District Cooling system using thermodynamic principles which incorporate actual data in assessing the cost rates of power and chilled water